A Rescued Legacy and a Jazz Model: Mapping Kant’s “Critique of Aesthetic Judgment”’s Twentieth- Century Reception - Gristina, Silvestre (Con-Textos Kantianos. International Journal of Philosophy, 2020)
Review of: Marino, Stefano, Terzi, Pietro (edited by), Kant’s “Critique of Aesthetic Judgment” in the 20th Century. A Companion to Its Main Interpretations, Berlin/Boston, Walter De Gruyter, 2020, pp. 361, ISBN 978-3-11-059613-7.